20th century media and the American psyche : a strange love - Corsbie-Massay, Charisse L'Pree, 1981- (London ; New York : Routledge, 2020)
"This innovative text bridges media theory, psychology, and interpersonal communication by describing how our relationships with media emulate the relationships we develop with friends and romantic partners through their ability to replicate intimacy, regularity, and reciprocity. In research-rich, conversational chapters, the author applies psychological principles to understand how nine influential media technologies - theatrical film, recorded music, consumer market cameras, radio, network and cable television, tape cassettes, video gaming, and dialup internet service providers - irreversibly changed the communication environment, culture, and psychological expectations that we then apply to future media technologies. With special attention to mediums absent from the traditional literature, including recorded music, cable television, and magnetic tape, this book encourages readers to critically reflect on their own past relationships with media and consider the present environment and the future of media given their own personal habits. 20th Century Media and the American Psyche is ideal for media studies, communication, and psychology students, scholars, and industry professionals, as well as anyone interested in a greater understanding of the psychological significance of media technology, usage, and adoption across the past 150 years"--
OCLC-licensed vendor bibliographic record.
Keywords: Mass media -- United States -- Psychological aspects; Mass media -- Social aspects -- United States; LANGUAGE ARTS & DISCIPLINES / Communication